2020
DOI: 10.1111/dth.13923
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of COVID‐19 pandemic on hair diseases through a web‐based questionnaire

Abstract: Aim Current quarantine conditions are a difficult process for individuals and can worsen the psychological state. Increased psychosocial stress can affect the course of many common “stress‐sensitive” skin conditions. This study examined the possible effects of COVID‐19 on hair and scalp diseases such as telogen effluvium (TE), alopecia areata (AA), and seborrheic dermatitis (SD) in individuals who had to stay at home for a long time and the patients’ methods of dealing with these diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 23 publications
(39 reference statements)
6
63
1
3
Order By: Relevance
“…Surprisingly, many patients (mainly women) spontaneously reported significant hair loss, which may correspond to a telogen effluvium , secondary to viral infection and/or a stress generated by the hospitalization and the disease. 6 Nevertheless, HRQoL was quite satisfactory, as most patients who had a professional activity before the infection went back to work.…”
mentioning
confidence: 95%
“…Surprisingly, many patients (mainly women) spontaneously reported significant hair loss, which may correspond to a telogen effluvium , secondary to viral infection and/or a stress generated by the hospitalization and the disease. 6 Nevertheless, HRQoL was quite satisfactory, as most patients who had a professional activity before the infection went back to work.…”
mentioning
confidence: 95%
“…2 In addition, dermatitis patients who have skin problems like hair and scalp diseases usually needed to take treatment from hospitals now also suffering from this situation. 3 With the increase of internet users around the globe, Infodemiology has become a very useful informatics method, especially for epidemic and pandemic situations. The Infodemiology study provides real-time surveillance in the health system by Google Trends which has already been used for studying epidemics like the 2009 influenza.…”
Section: Introductionmentioning
confidence: 99%
“…The other type of hair loss that may be seen in COVID-19 condition is telogen effluvium, which is recognized by sporadic hair loss, and the hair quickly enters the telogen stage due to conditions such as systemic disorders, stressful situations, medications, nutrient deficiencies, and surgeries [ 44 ]. The results of an observational/cross-sectional study on 563 participants during the COVID-19 pandemic, telogen effluvium were observed in 27.9% of the participants [ 45 ].…”
Section: Covid-19 Drugs and Hair Lossmentioning
confidence: 99%